Analisis Persepsi Mahasiswa Program Studi Matematika dalam Pembelajaran Online di Masa Pandemi Covid-19 - Nur'aini Muhassanah; Ambar Winarni; Afifah Hayati (ARITHMETIC: Academic Journal of Math, 2020)
The objectives of this study were to: (1) describe the perceptions of students in the Mathematics Study Program of the Faculty of Science and Technology, Purwokerto University of Nahdlatul Ulama (UNU) on learning interactions between students and students and students and lecturers; (2) describe the perceptions of students in the Mathematics Study Program of UNU Purwokerto about the learning environment in online learning. The subjects of this study were students in the 2nd and the 4th semester of the Mathematics Study Program of UNU Purwokerto. This research was conducted in April - June 2020. The data in this study were obtained from questionnaires and interviews. . The subjects in this study were taken by purposive sampling technique. The data validation used the triangulation method. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results showed the following: 1) students had difficulty in interacting with fellow students and lecturers in online lectures. This is evidenced by the high level of presentation which shows disagreement with the statement that says student interaction in online lectures has gone well; 2) students response to the learning environment in online lectures, it can be concluded that the learning environment in online lectures has not supported students to learn.